2017
DOI: 10.1371/journal.pone.0177327
|View full text |Cite
|
Sign up to set email alerts
|

Manifold implications of obesity in ischemic heart disease among Japanese patients according to covariance structure analysis: Low reactivity of B-type natriuretic peptide as an intervening risk factor

Abstract: Background/ObjectivesObesity is believed to be one of the major risk factors for cardiovascular disease in Western countries. However, the effects of obesity should be continuously examined in the Japanese population because the average bodily habitus differs among countries. In this study, we collectively examined the significance of obesity and obesity-triggered risk factors including the low reactivity of B-type natriuretic peptide (BNP), for ischemic heart disease (IHD) in Japanese patients.Methods and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Because of the cardio-protective effects exerted by BNP, we hypothesized that the increased risk of IHD in individuals with obesity is due not only to well-known risk factors (e.g., hypertension, dyslipidaemia, diabetes) but also to the compromised cardio-protection of the reduced BNP level. By a covariance structure analysis in 1,252 patients with cardiac disorders, we confirmed that low BNP level, as well as hypertension, dyslipidaemia and haemoglobin A1c (HbA1c), but not body mass index (BMI) was significantly associated with the incidence of IHD (p < 0.001) 16 . To confirm this hypothesis further, by using cTnI as an indicator of cardiac disorders in this study, we assessed whether low BNP level was associated with an enhanced cardiovascular risk in the general population.…”
Section: Introductionmentioning
confidence: 62%
“…Because of the cardio-protective effects exerted by BNP, we hypothesized that the increased risk of IHD in individuals with obesity is due not only to well-known risk factors (e.g., hypertension, dyslipidaemia, diabetes) but also to the compromised cardio-protection of the reduced BNP level. By a covariance structure analysis in 1,252 patients with cardiac disorders, we confirmed that low BNP level, as well as hypertension, dyslipidaemia and haemoglobin A1c (HbA1c), but not body mass index (BMI) was significantly associated with the incidence of IHD (p < 0.001) 16 . To confirm this hypothesis further, by using cTnI as an indicator of cardiac disorders in this study, we assessed whether low BNP level was associated with an enhanced cardiovascular risk in the general population.…”
Section: Introductionmentioning
confidence: 62%
“…The indirect effect was determined by multiplying the path coefficients of the intervening variables. Recently, we reported our research by applying a covariance structure analysis 19–24. In addition, as covariance structure analysis consists partly of the Bayesian estimation method and the Bayesian adaptive trial design, Bayesian structural equation modelling successfully gave a description of this result, and it is expected to be a next-generation statistical procedure for mega-trials 28.…”
Section: Methodsmentioning
confidence: 97%
“…Serum biochemical analyses and plasma BNP level measurements were performed in a central laboratory in our hospital during the study. Plasma BNP level was measured as described in previous reports 14 15 19 20 23. In brief, whole blood (5 mL) was collected in tubes containing ethylenediaminetetraacetic acid disodium salt (1 mg/mL blood).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the path model described in www.nature.com/scientificreports www.nature.com/scientificreports/ as the degree of obesity becomes more severe 23,34 . Importantly, we also reported that the plasma BNP levels were relatively low in patients with chronic IHD compared with those of non-IHD patients 35 and that the low reactivity of BNP could play a causative role in IHD 36 . We believe that treatment of obesity will be beneficial for preventing IHD in part by increasing endogenous natriuretic peptide levels.…”
Section: Scientific Reports |mentioning
confidence: 56%